Pemberian Ekstrak Bubuk Kakao (Theobroma cacao L.) pada Model Tikus Fase Retensi Ortodonti terhadap Jumlah Osteoblas dan Osteoklas - Adelia Hidayat (Fakultas Kedokteran Gigi, 2026)
Introduction: Malocclusion requires orthodontic treatment followed by a retention phase to maintain tooth position and prevent relapse. The stability of orthodontic outcomes is closely related to alveolar bone remodeling, which involves a balance between osteoblast-mediated bone formation and osteoclastmediated bone resorption. Cocoa (Theobroma cacao L.) contains bioactive compounds that may influence bone metabolism; however, its effect on osteoblast and osteoclast activity during the retention phase remains unclear. Aim: To evaluate the effect of cocoa powder extract on the number of osteoblasts and osteoclasts in an orthodontic retention rat model. Methods: This study was an experimental laboratory study using Wistar rat models subjected to orthodontic treatment followed by a retention phase. The treatment group received systemic administration of cocoa powder extract. Samples were collected at days 3, 7, and 14 after the retention phase. Histological analysis using Hematoxylin-Eosin staining was performed to assess the number of osteoblasts and osteoclasts. Result: The treatment group showed a significant increase in osteoblasts, while the decrease in osteoclasts was not statistically significant at all observation time points. Conclusion: Administration of cocoa powder extract during the orthodontic retention phase tended to enhance bone formation and reduce bone resorption.
:: Finalisasi repositori 15 Juli 2026_Kurnadi
Keywords: alveolar bone remodeling; osteoblast; osteoclast; cocoa powder extract; retention